2011
DOI: 10.1523/jneurosci.1639-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Motor Neuron Cell Death through DNA Methylation

Abstract: DNA methylation is an epigenetic mechanism for gene silencing engaged by DNA methyltransferase (Dnmt)-catalyzed methyl group transfer to cytosine residues in gene regulatory regions. It is unknown if aberrant DNA methylation can cause neurodegeneration. We tested the hypothesis that Dnmts can mediate neuronal cell death. Enforced expression of Dnmt3a induced degeneration of cultured NSC34 cells. During apoptosis of NSC34 cells induced by camptothecin, levels of Dnmt1 and Dnmt3a increased five-fold and two-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
301
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 327 publications
(322 citation statements)
references
References 75 publications
19
301
2
Order By: Relevance
“…Several nearby glial cells (round nuclei) have low or undetectable 5mC. The details of this study showing changes in human ALS motor cortex compared with agematched controls have been reported [70]. Scale bars: panorama 17 μm; inset 8 μm where it is thought to oppose the role of 5mC-mediated transcriptional repression by inhibiting the binding of methyl-CpG binding protein-2 and other DNA binding proteins; thus, 5hmC functions as a facilitator of geneexpression activity [44].…”
Section: Dna Methylation As An Epigenetic Mechanismmentioning
confidence: 57%
See 4 more Smart Citations
“…Several nearby glial cells (round nuclei) have low or undetectable 5mC. The details of this study showing changes in human ALS motor cortex compared with agematched controls have been reported [70]. Scale bars: panorama 17 μm; inset 8 μm where it is thought to oppose the role of 5mC-mediated transcriptional repression by inhibiting the binding of methyl-CpG binding protein-2 and other DNA binding proteins; thus, 5hmC functions as a facilitator of geneexpression activity [44].…”
Section: Dna Methylation As An Epigenetic Mechanismmentioning
confidence: 57%
“…A possibility is that Dnmts in the adult mammalian brain re-methylate newly incorporated cytosines from G-T mismatch DNA repair after 5mC deamination [67]. We have found that Dnmt1 and Dnmt3a have distinct subcellular localizations in neurons [70], suggesting non-redundant functions. Our discovery that Dnmt3a, but not Dnmt1, is located in presynaptic axon terminals in the adult CNS is exciting because it identifies a local presynaptic possibility for Dnmt3a in regulating synaptic function.…”
Section: Mammalian Dnmts In the Central Nervous Systemmentioning
confidence: 86%
See 3 more Smart Citations